Influence of patient characteristics on survival following treatment with helical stereotactic body radiotherapy (SBRT) in stage I non‐small‐cell lung cancer. Issue 1 (4th February 2013) - Fischer‐Valuck, Benjamin W.; Durci, Michael; Katz, Sanford R.; Wu, Hsinshun Terry; Syh, Joseph; Syh, Jarron; Patel, Bijal; Rosen, Lane R.
Abstract Background: To determine the influence of patient and tumor characteristics on clinical outcomes in patients with early‐stage non‐small cell lung cancer (NSCLC) treated with helical intensity modulated stereotactic body radiotherapy (SBRT). Methods: From March 2005 to August 2010 a total of 62 patients with biopsy proven Stage I NSCLC underwent helical SBRT with 48 Gy in 4 fractions or 60 Gy in 5 fractions. Patient and tumor characteristics including tumor stage, age, sex, tumor histology, maximal tumor diameter, and smoking history, were evaluated in regard to local control and overall survival using Kaplan‐Meier survival curves and the Cox proportional hazard method. Treatment related toxicity in the patient subgroups was evaluated. Results: The median follow‐up was 28 months. Total cohort local control was 93.55% and 3‐year overall survival (OS) was 53.4%. Those patients with Stage IA disease had a 3‐year OS of 64.4% versus 32.1% for Stage IB disease (P = 0.042). Tumors classified as T1a (≤20 mm) and T1b (20–30 mm) had significantly increased overall survival compared to T2 (>30 mm) tumors (P = 0.046). There was a slight survival advantage in those patients with adenocarcinoma. No correlation between age, gender or smoking history, and overall survival was found. Nine patients had radiation related toxicity, which was increasingly more common with advancing age. Conclusion: Helical SBRT is an effective method to treat NSCLC and the most significant prognostic factors were tumor stage and size. There was no correlation between age, gender, and smoking history.